Aplicativização, causativização e nominalização: uma análise unificada de estruturas argumentais em Tenetehára-Guajajára (Família Tupí-Guaraní) - Quesler Fagundes Camargos (2017)
This doctoral dissertation aims to investigate the functions of VoiceP and vPCAUSE. The main source of data is the Tenetehára-Guajajára language (Tupí-Guaraní Linguistic Family), with the data collected during fieldwork conducted between 2012 and 2015 in the Arariboia and Caru Indigenous Lands (located in the State of Maranhão, Brazil). A theoretical proposal will be presented to unify the grammatical phenomena of applicativization, causativization and nominalization in the Tenetehára-Guajajára language. According to Pylkkänen (2002, 2008), many of the original functions of the vP (CHOMSKY, 1995) have been divided between two independent projections: VoiceP and vPCAUSE. In this work, I will provide an overview of the argumentation concerning the roles ascribed to the VoiceP projection. These include: introduction of the external argument (agent argument) and checking of the abstract Case of the internal argument. The vPCAUSE projection, in turn, has the function of introducing causative meaning. I will investigate the implications for the Tenetehára-Guajajára language of the hypothesis that some languages project VoiceP and vPCAUSE independently. For example, derived causative transitive verbs do not project VoiceP if the applicative morphology {eru-} participates in the derivation. The best evidence comes from sentences with no external argument, although the causative morphology {mu-} is present. The same holds for causative transitive verbs when they are nominalized. Therefore, the Tenetehára-Guajajára language projects VoiceP and vPCAUSE independently, and the introduction of the external argument is syntactically disassociated from the introduction of causative meaning.